Kinerja Efisiensi Energi Terhadap Manajemen Biaya Operasional Gedung - Dano Quinta Revana; Wisnumurti Wisnumurti; Agung Murti Nugroho (Rekayasa Sipil, 2018)
The concept of Green Building is one of the efforts to reduce the effects of global warming through developmental aspects. Excessive energy consumption becomes an issue of global warming and waste of operational cost in the building so that this research will conduct an assessment using GREENSHIP and SNI parameters in Building E Faculty of Administration Brawijaya University expected to know the level of "green" in energy efficiency criteria. Energy Consumption Intensity in this building is 60,65 kWH/ m2/ year. Some rooms have the use of electric power exceeding the maximum SNI power, so there needs to be a reduction of wattage bulbs and lamp replacements with LED lights that can save power 2.039,04 kWH and saving the operational cost Rp. 1.935.218,88 every month